2010
DOI: 10.1097/mcc.0b013e32833e9718
|View full text |Cite
|
Sign up to set email alerts
|

Family satisfaction with critical care: measurements and messages

Abstract: Assessing and analyzing family satisfaction in the ICU ultimately will support healthcare professionals in their continuing effort to improve care of critically ill patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 73 publications
2
60
1
8
Order By: Relevance
“…Physical presence at the bedside during rounds may be the most desired iteration of family presence, but widespread adoption of telemedical technology now makes virtual presence a feasible alternative when physical presence is not possible. Providers and family members in the study expressed how a virtual presence would not be a substitute for family member's physical presence, but suggested it might [26][27][28] Moreover, virtual family participation could in some cases lead to earlier discussions about end-of-life care. In one recent study, 29 clinicians reported that lack of both patients' decisionmaking capacity and substitute decision makers were important barriers to discussions about the goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…Physical presence at the bedside during rounds may be the most desired iteration of family presence, but widespread adoption of telemedical technology now makes virtual presence a feasible alternative when physical presence is not possible. Providers and family members in the study expressed how a virtual presence would not be a substitute for family member's physical presence, but suggested it might [26][27][28] Moreover, virtual family participation could in some cases lead to earlier discussions about end-of-life care. In one recent study, 29 clinicians reported that lack of both patients' decisionmaking capacity and substitute decision makers were important barriers to discussions about the goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…The survey completed by family members was composed from 3 different sources: the Critical Care Needs Inventory (CCNI), 2,3 the Family Satisfaction in the ICU (FS-ICU) survey, [31][32][33][34][35] and investigatordeveloped statements specific to the neuroscience ICU at the facility. Total time to complete the paper and pencil survey was less than 15 minutes.…”
Section: Family Member Needs Surveymentioning
confidence: 99%
“…The original FS-ICU survey was a 34-item listing of various aspects or components of patient care in the ICU, 31,32 later revised to a 24-item survey. [33][34][35] Family members rate how well they perceived care delivery for each aspect or component on a 5-level Likert scale (1 = excellent, 2 = very good, 3 = good, 4 = fair, 5 = poor). The FS-ICU is a valid and reliable survey tool.…”
Section: Family Member Needs Surveymentioning
confidence: 99%
“…Family satisfaction was measured by the FS-ICU [2][3][4], a much used and previously validated tool, while patient satisfaction was elicited by using an adapted version of this questionnaire. A similar approach has been taken previously by a Swiss group [5].…”
mentioning
confidence: 99%